Pengaruh Gender, Ketenagakerjaan, Kemiskinan, dan Pendidikan Terhadap IPM NTT 2020-2024 - Fahira Febi Setyastuti; Rakhmat Priyono; Dwita Aprillia Floresti (Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2026)
The Province of East Nusa Tenggara (NTT) faces human development challenges, reflected in its relatively low Human Development Index (HDI) and regional disparities, influenced by poverty, unemployment, gender inequality, and educational participation. This study analyzes the effects of gender inequality, Labor Force Participation Rate (LFPR), Open Unemployment Rate (OUR), poverty, and School Participation Rate (SPR) on HDI during 2020–2024 using panel data regression with a Fixed Effect Model (FEM) based on BPS data. The results show all variables are simultaneously significant; partially, poverty and OUR have a negative significant effect, SPR has a positive significant effect, while gender inequality and LFPR are not significant, highlighting the importance of economic and educational factors in improving HDI.